Application of Electrocoagulation Process for Continuous Coal Stockpile Wastewater Treatment System - Rusdianasari Rusdianasari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Coal wastewater is characterized by high total suspended solid (TSS), heavy metals, and low acidity (pH). The purpose of this study was to research the effects of the operating parameters such as applied voltage, the number of electrodes, and reaction time on a real coal stockpile wastewater in the continuous electrocoagulation process. For this purpose, aluminum electrodes were used in the presence of potassium chloride as an electrolyte. It has been shown that the removal efficiency of TSS and heavy metals content increased with increasing the applied voltage and reaction time. The results indicate that the electrocoagulation process is efficient and able to achieve 88.67% TSS removal, 95.65% ferrous removal, 99.11% manganesse removal, and pH increased until 7.1 at 24 volts during 120 min, respectively. The experiments demonstrated the effectiveness of electrocoagulation methods for the treatment of coal stockpile wastewater.Key words: coal stockpile wastewater, electrocoagulation, electrode